Leveraging applications of formal methods, verification and validation. 7th International Symposium, ISoLA 2016, Imperial, Corfu, Greece, October 10-14, 2016, Proceedings /: 7th International Symposium, ISoLA 2016, Imperial, Corfu, Greece, October 10-14, 2016, Proceedings. discussion, dissemination, applications : Part II, (2016) - Unknown
No abstract available